Mechanisms of Invasion in Glioblastoma: Extracellular Matrix, Ca2+ Signaling, and Glutamate - So, Jae-Seon; Kim, Hyeono; Han, Kyung-Seok (Frontiers in Cellular Neuroscience, 2021)
Glioblastoma multiforme (GBM) is the most common and malignant form of primary brain tumor with a median survival time of 14-16 months in GBM patients. Surgical treatment with chemotherapy and radiotherapy may help increase survival by removing GBM from the brain. However, complete surgical resection to eliminate GBM is almost impossible due to its high invasiveness and metastases. When GBM cells migrate to the brain, they interact with various cells, including astrocytes, neurons, endothelial cells, and the extracellular matrix (ECM). They can also make their cell body shrink to infiltrate into narrow spaces in the brain; thereby, they can invade regions of the brain and escape from surgery. Brain tumor cells create an appropriate microenvironment for migration and invasion by modifying and degrading the ECM. During those processes, the Ca2+ signaling pathway and other signaling cascades mediated by various ion channels contribute mainly to gene expression, motility, and invasion of GBM cells. Furthermore, GBM cells release glutamate, affecting migration via activation of ionotropic glutamate receptors in an autocrine manner. This review focuses on the cellular mechanisms of glioblastoma invasion and motility related to ECM, Ca2+ signaling, and glutamate. Finally, we discuss possible therapeutic interventions to inhibit invasion by GBM cells.